X-band Operations Metamaterial Absorber with Extended Circular Ring Topology for Size Reduction - M. M. Gajibo; M. K. A. Rahim; N. A. Murad; O. Ayop; B. D. Bala; H. A. Majid (Institute of Advanced Engineering and Science, 2017)
A metamaterial electromagnetic wave absorber consisting of a big circular ring patch with four smaller suppression circular rings is presented in this report. The metamaterial electromagnetic wave absorber introduces the concept of size reduction by suppressing the resonance frequency. An FR4 substrate was used and the incidental wave angles were varied from 00 to 600. Simulations results shows peak absorption of 100% was achieved at 10.7 GHz by the absorber for both TE and TM polarization incident waves. Minimum absorption for both TE and TM mode of 90.6% was achieved under TE mode. The metamaterial absorber was being tested with and Ultra-wide band antenna and the results were reported.